Kinematic and electromyographic features of upper-limb movement performed by healthy and post-stroke patients - Silva, Rosa Mariana (2021)
It is extremely difficult to simplify the relation between several body parts, which perform human motion, into one set of features. Mainly, the upper-limb is capable of a wider range of actions, going from fine manipulation to prehension and grasping. Aiming to describe its complexity, several studies have been conducted in order to better understand the upper-limb specificities. However, most of studies restrain the task to pointing, reaching, or grasping, which seems not enough to explain the wide range of tasks possible to be performed in a daily scenario.